Assessing conservation efforts of mangrove forest in Delta Tumpat Kelantan. Issue 1 (1st November 2022) - Jemali, N J N; Rahim, A A; Majid, S; Muhammad, M; Susanti, S; Abong, N N D; Nordin, S M; Yusof, M
Abstract : Mangrove forest hosts a variety of biodiversity and offers a great coastal ecosystem function. Despite the importance of mangrove ecosystems, they are being destroyed more quickly than all other types of forests around the world for development as predicted in many studies. The loss of mangrove areas due to aquaculture activities, rural settlements, and sediment accretion had caused the Delta Tumpat Mangrove Forest (DTMF), Kelantan in a dangerous state. Due to this alarming situation, many conservation efforts have been taken by both government and private agencies. This paper explores the impact of mangrove conservation efforts of DTMF from 2000 to 2019. Based on evaluation on the two decades data, more than 100, 000 mangrove trees were planted within 31 officially recorded programs with a planting average of 3861 trees per program. Rhizophora apiculata and Rhizophora mucronata are the main species planted in the 42 ha of the area including small islands at DTMF. The conservation initiative and tree planting program have mainly gauged the Kelantan Forestry Department's work in partnership with other agencies as well as the involvement of the communities. Further research on human socioeconomic concerns on conservation priorities can help to ensure the long-term sustainability of mangrove forests in the future.